Simplification of Income Tax Withholding Article 21 Through the Application of Average Effective Rates for Individual Taxpayers - Wasesa, Tjandra; Toni, Sugiharto Heri; Karnaen, Bambang; Zuhroh, Diana; Dewi, Rina (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2024)
Calculation of Income Tax and PPh 21 withholding is quite complex and has a confusing calculation scheme so it is necessary to simplify and simplify calculations and deductions, as well as administrative management that does not burden taxpayers in carrying out their tax obligations correctly. In addition to progressive tax rates, the Directorate General of Taxes has implemented changes to the PPh 21 withholding rates using the average effective rate (TER) scheme in accordance with Government Regulation Number 58 of 2023. Find out about the new scheme and the latest example of PPh 21 calculations which will be effective starting in 2024. With the tariff scheme Effective PPh 21 TER, the calculation of Income Tax Article 21 becomes simpler. The TER scheme also does not change the calculation of PPh 21 in a year, because it is still based on Article 17 paragraph (1) letter a of the Income Tax Law. Apart from that, the TER scheme also does not provide additional new tax burdens because it is basically a method of calculating taxes on a monthly or daily basis.